Seismic properties of the permafrost layer using the HVSR method in Seymour-Marambio Island, Antarctica - Vargas, Carlos A. (2022)
Authors have calculated the H/V spectral ratios using seismic-noise recordings in the uppermost layers north of the Seymour-Marambio Island, Antarctic. Sixty-seven seismic site-response measurements near and far from the Argen-tinean Marambio Base runway suggest geotechnical works on the uppermost sedimentary layers due to maintenance, landing, and taxi of large loads and aircraft during decades could contribute to changes in their seismic dynamic response. Two horizontal images of Vp, Vs, and Vp / Vs ratios at 1.0 m and 35.0 m depth show lateral variations in the permafrost properties. Authors interpret that permafrost is emplaced in rocks with different porosities and contrasting fluids saturation at those depths. In shallow strata, the saturation of gases affects mainly the elastic properties. In dee-per strata, where the location of water reservoirs is detected, the primary mechanism of seismic dissipation is anelastic.